(untitled) (Bangladesh Heart Journal, 2022)
Background: The pandemic existence of corona virus disease 2019 (COVID -19) in the year 2020 has initially limited the number of intervention in cardiac diseases in our country. The need for placement of permanent pacemaker is a medical emergency but in patients with concomitant COVID -19, it’s a double edged sword. The treatment strategy and planning for this group of patients with high degree atrioventricular block (AVB) or sinus node disease (SND), needing permanent pacemaker is the fundamental concern along with the safety of the attending cardiologists and other staff members. In this study we sought to comprehend the treatment strategies in patients requiring pacemaker with simultaneous COVID-19 co-infection. Methods: This study was done at the National institute of cardiovascular diseases (NICVD), Shere Bangla Nagar, Dhaka from 10th March 2020 to 9th September 2020. During these six months all patients waiting for permanent pacemaker implantation were screened for COVID-19 by real time polymerase chain reaction (RT PCR). The positive cases were included in the study and managed according to the in hospital protocol. Results: A total of 98 patients had permanent pacemaker implanted during this period, among them12 patients (12.24%) were tested positive for COVID-19. Average age of the patients was 68±7.6 years and 66.7% was male and 33.3% was female. The mean duration of RT PCR positive status was 20.6±6.4 days (range 14 to 29 days) and the mean duration of indwelling TPM was 21.25±7.05 days (range 17 to 30 days). There was no TPM related complication following PPM implantation. Conclusions: Conservative approach of medical management with TPM for stabilization of the patients with corona virus disease is a safe option for delayed PPM implantation after improvement of the patients. In hospital treatment protocol with facilities for isolation and treatment of COVID is the mainstay of the treatment strategy. Bangladesh Heart Journal 2022; 37(1): 59-64